The Relationship between Pregnant Women's Knowledge and Attitude with the Implementation of the Delivery Planning and Complication Prevention Program (P4K) in the Work Area of the Grogol Community Health Center, Kediri Regency - Yuni Sevina Saputri; Lumastari Ajeng Wijayanti; Ririn Indriani (Journal Of Nursing Practice, 2026)
Background: The Birth Planning and Complication Prevention Programme (P4K) aims to improve access to and the quality of maternal and newborn health services by promoting birth preparedness and preventing pregnancy-related complications. Purpose: Maternal knowledge and attitudes are important factors influencing the implementation of P4K. A preliminary survey conducted at Puskesmas Grogol found that P4K coverage had not achieved the expected target and that 70% of ten interviewed pregnant women were unaware of the P4K programme. Methods: This study employed a correlational design with a cross-sectional approach. The study included 42 third-trimester pregnant women selected using simple random sampling. Data were collected using structured questionnaires and analysed using Spearman's rank correlation test. Results: Of the 42 respondents, 54.8% had good knowledge of P4K, while 52.4% had moderately positive attitudes toward the programme. Spearman's rank correlation analysis showed a statistically significant relationship between maternal knowledge and P4K implementation (p = 0.002) and between maternal attitudes and P4K implementation (p = 0.032). Both p-values were less than 0.05. Conclusion: Maternal knowledge and attitudes were significantly associated with the implementation of the Birth Planning and Complication Prevention Programme (P4K). These findings suggest that improving maternal knowledge and fostering positive attitudes may enhance P4K implementation, thereby supporting better birth preparedness and maternal health services.